To solve for the measure of angle \( m∠BAC \), we can use the fact that ray \( AC \) bisects angle \( A \).
Given that:
- \( m∠BAD = 46^\circ \)
Since ray \( AC \) bisects \( ∠A \), we know that:
- \( m∠BAC = m∠CAD \)
Therefore, the total measure of angle \( A \) can be represented as: \[ m∠BAC + m∠CAD = m∠BAD \]
Since \( m∠BAC = m∠CAD \), we can express this as: \[ 2 \cdot m∠BAC = m∠BAD \] \[ 2 \cdot m∠BAC = 46^\circ \] \[ m∠BAC = \frac{46^\circ}{2} = 23^\circ \]
Thus, the measure of angle \( m∠BAC \) is \( 23^\circ \).
The correct response is: The m∠BAC is 23 degrees.